2008
DOI: 10.1111/j.1365-2311.2007.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation of the aphid pathogenic fungus Pandora neoaphidis by the invasive coccinellid Harmonia axyridis

Abstract: 1. The ladybird Harmonia axyridis is an invasive alien species in many countries and is predicted to have a negative impact on native biodiversity. However, little is known on the status of this aphidophage as an intraguild predator of natural enemies of aphids such as insect‐pathogenic fungi.2. The study assessed the predation of the aphid‐specific pathogenic fungus Pandora neoaphidis by adult and larval H. axyridis collected from the U.K. (an invasive population) and Japan (a native population) relative to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…There has been less research on the interactions between H. axyridis and species within the 347 aphidophagous guild beyond ladybirds (Pell et al 2008 (Roy et al 2008a) whereas most other aphid 354 predators avoid consumption of infected aphids (Roy et al 1998)…”
mentioning
confidence: 99%
“…There has been less research on the interactions between H. axyridis and species within the 347 aphidophagous guild beyond ladybirds (Pell et al 2008 (Roy et al 2008a) whereas most other aphid 354 predators avoid consumption of infected aphids (Roy et al 1998)…”
mentioning
confidence: 99%
“…Specifically Roy et al (2008b) demonstrated that H. axyridis from a 513 culture derived from Japan were less likely to consume aphid cadavers supporting the 514 beneficial aphid-specific fungal pathogen P. neoaphidis than those derived from the UK. 515 They speculated that H. axyridis obtained from non-native populations were derived from 516 biological control cultures and, through microevolution or founder effects, have been, 517 perhaps unintentionally, selected for extreme polyphagy and an increased tendency 518 towards intraguild predation compared to H. axyridis in its native range (Roderick and 519 Howarth 1999; Hufbauer and Roderick 2005; Roy et al 2008a). It would be extremely 520 interesting to compare the strength and symmetry of intraguild interactions between 521 Japanese, UK and US derived H. axyridis for a wider range of guild members, from both 522 native and non-native ranges to determine if they function differently in relation to all guild 523 members with which they compete.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…As the sporulating aphid cadaver is sessile, it is an easy prey 301 item for generalist predators. In a laboratory study, Roy et al (2008a) assessed the pre-302 dation of aphid cadavers sporulating with Pandora neoaphidis (Remaudière and 303 Hennebert) Humber (Zygomycetes: Entomophthorales) by UK and Japanese-derived…”
mentioning
confidence: 99%
“…For example, the invasive H. axyridis is more likely than the native Coccinella septempunctata (seven-spot ladybird) to consume the cadavers of Pandora neoaphidis fungus-infected aphids (Roy et al 2008a), a form of intraguild predation. Although study of other members of the aphidophagous and coccidophagous guilds is lacking, evidence indicates that H. axyridis may affect the population of P. neoaphidis more negatively than would C. septempunctata, leading to a greater competitive advantage for H. axyridis.…”
Section: Unique Invasiveness Trait Groups Of Insectsmentioning
confidence: 99%